1963
DOI: 10.1017/s0068246200001677
|View full text |Cite
|
Sign up to set email alerts
|

Underground Drainageways in Southern Etruria and Northern Latium

Abstract: The River Tiber at Rome flows between the gentle, converging slopes of two extinct volcanoes, the M. Sabatini to the northwest and the complex known as the Alban Hills to the southeast. On the southern flanks of the M. Sabatini lie the Etruscan cities of Veii and Caere (modern Cerveteri) as well as many smaller Etruscan settlements. To the south on the western and southern slopes of the Alban Hills are such ancient towns of northern Latium as Ardea, Lanuvio and Velletri. In these same areas is an extensive dev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

1988
1988
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(13 citation statements)
references
References 1 publication
0
13
0
Order By: Relevance
“…There is a unique example of substantial rock-cut houses at Luni in the Mignone valley (Ostenberg 1967), but whilst the acropolis formed by the natural outcrop at the site measures 5 ha, the Apennine Bronze Age settlement was restricted to the area of the houses, an area very similar to the other settlements. This dispersed settlement system may in part have been a response to the trend to aridity that is fairly well documented for the later 2nd millennium BC in the Etrurian pollen diagrams (Bonatti 1961;1963;1970;Frank 1969;Hunt 1988). Underwater archaeology has shown that at this time, too, the volcanic lakes of South Etruria were ringed with small Apennine Bronze Age settlements (Fugazzola Delpino 1982).…”
Section: The Pre-etruscan Countrysidementioning
confidence: 83%
“…There is a unique example of substantial rock-cut houses at Luni in the Mignone valley (Ostenberg 1967), but whilst the acropolis formed by the natural outcrop at the site measures 5 ha, the Apennine Bronze Age settlement was restricted to the area of the houses, an area very similar to the other settlements. This dispersed settlement system may in part have been a response to the trend to aridity that is fairly well documented for the later 2nd millennium BC in the Etrurian pollen diagrams (Bonatti 1961;1963;1970;Frank 1969;Hunt 1988). Underwater archaeology has shown that at this time, too, the volcanic lakes of South Etruria were ringed with small Apennine Bronze Age settlements (Fugazzola Delpino 1982).…”
Section: The Pre-etruscan Countrysidementioning
confidence: 83%
“…The landscape was not opened up as much as in the Roman period, but pollen studies show that, at least at a local level, the vegetation was manipulated not only to provide cereal and tree crops, but also grazing for sheep, cattle, and pigs (Stoddart et al, 2019). In the area around the city of Veio, watercourses were manipulated to ensure the provision of sufficient water for crops, and many cities show the construction of wells and drainage systems to maintain a high living standard (Judson and Kahane, 1963). Some cities such as Veio in the south and probably Chiusi in the north specialized in agricultural production.…”
Section: From Large Data To Urban Anthropologymentioning
confidence: 99%
“…Underground engineering was crucial for the protection of the water system from both pollution and enemy incursions in Rome as well as in other Italian and European sites [41,42]. In particular, they developed qanat-type technologies in the construction of utility tunnels for the water supply of urban sewage systems [43], like the grandiose urban sewerage system of the sewers of Rome, with ducts characterized of a large cross-section and still in operation, and several lesser but similar implementations found in present in Luxembourg, Croatia, Portugal, Germany, Italy, Greece and Spain [1,6,[44][45][46][47][48][49].…”
Section: Roman Aqueducts and Cisternsmentioning
confidence: 99%
“…Its construction started in 1743 and was accomplished between 1743 and 1778, result of the reconstruction of a preexisting viaduct of which the existence was first documented by historical sources in 1686 but postulated dating back to the Roman period [74,75]. Over 3500 m long, it is one of the best preserved underground man-made structures for collection and transport of water resources in southern Italy, draining the waters issuing at the contact between Plio-Pleistocene calcarenites and the overlying clays, with clear differences in permeability [45]. A number of inspection wells go down to a system of underground galleries developing at different heights.…”
Section: Underground Hydro-technologies In Early-and Mid-modern Timesmentioning
confidence: 99%